Pre-ethics According in Taoism Philosophy - Safe, Ali (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research is based on the basic idea Taoist philosophy pioneered by the wise Chinese scholar, lao Tsu,- presented amoral theory that is unlike any other ethical theories and Philosophy is a concept of non-action, i.e, spontaneous and un-intentional action un- intentionality and spontaneousity are the foundation of any human action, which is why lao tsu considers it precedential to morality because morality is a deliberate, conscious, purposive act, it is an artificial act lao tsu invitation precedes this act. Therefore, the non-action is the main character of the tao itself (the absolute tao), which grants mankind and the universe age distinction, so it was a must to pave for our basic idea through an important introduction of the tao and Taoism reaching the induction of everything that points to our basis hypothesis: the ethical theory of Taoism is considered pre-moral or superior to what is known of moral frameworks and systems.